Complex Estimation of Organic Production Potential in Region (illustrated by Sakha Republic (Yakutia) - N. P. Vasiliev (Вестник Российского экономического университета имени Г. В. Плеханова)
The article proposes methodology of complex estimation of developing organic production in the region on the basis of objective indicators. The research was done based on statistic data of the Territorial Body of Rosstat on Sakha Republic (Yakutia), reports and data of the Ministry of Agriculture and Food Policy of Sakha Republic (Yakutia), the Ministry of Economy of Sakha Republic (Yakutia), GKU ‘The Center of Resource Support for Agro-Industrial Complex in Sakha Republic (Yakutia)’. Statistic methods were used for the estimation. The research showed 36 municipal entities of the Republic. Methodology combines 53 indicators divided onto 5 blocks: social and economic, plant-growing, stock-breeding, wild plants and bee-keeping. The potential of organic production development was estimated in municipal entities of Yakutia. The research results show that only less than a forth of territories have an average or higher potential of organic production development and more than 75% of territories have the potential lower than the average one, where under populated regions of the Arctic zone are included.